Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.2.20678/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sarcopenia is associated with hypertension in older adults: a systematic review and meta-analysis

Abstract: Background: Sarcopenia and handgrip strength have been observed and correlated in association with hypertension among the old-age people. However, the results reported in different studies were inconsistent. In the current study, we conducted a systematic review and meta-analysis to reveal the significant association between sarcopenia, handgrip strength, and hypertension in older adults. Methods: PubMed, MEDLINE, Cochrane Library, and EMBASE databases were searched from inception to 15 November, 2019 to retri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Sarcopenia is one of the most prominent physiological changes related with aging, and is characterized by a gradual loss of muscle mass and function [7]. Sarcopenia may increase the risk for cognitive decline [8], and this relationship may be explained by shared pathophysiological mechanisms (e.g., inflammation [9,10], hormonal dysregulations [11,12] and malnutrition [13,14]), brain atrophy [15] and several mediating factors (e.g., depression [16,17], metabolic syndrome [18,19] and hypertension [20,21]). A systematic review and metaanalysis of 15 studies showed that sarcopenia was significantly and positively associated with cognitive impairment (odds ratio [OR]=2.25, 95% confidence interval [CI]=1.70-2.97) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is one of the most prominent physiological changes related with aging, and is characterized by a gradual loss of muscle mass and function [7]. Sarcopenia may increase the risk for cognitive decline [8], and this relationship may be explained by shared pathophysiological mechanisms (e.g., inflammation [9,10], hormonal dysregulations [11,12] and malnutrition [13,14]), brain atrophy [15] and several mediating factors (e.g., depression [16,17], metabolic syndrome [18,19] and hypertension [20,21]). A systematic review and metaanalysis of 15 studies showed that sarcopenia was significantly and positively associated with cognitive impairment (odds ratio [OR]=2.25, 95% confidence interval [CI]=1.70-2.97) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the development of effective drugs and regular adjustment of treatment have improved the prognosis of patients with rheumatoid arthritis (RA), comorbidities can reduce their survival and quality of life [1]. These negative outcomes may be due the increased prevalence of cardiovascular diseases and functional impairments in RA patients, which may be exacerbated by hypertension (HTN) [2]. HTN is more frequent in patients with RA than in the general population, with 62% of men and 47% of women with early RA having HTN [3].…”
Section: Introductionmentioning
confidence: 99%
“…HTN also increases the risk of cardiovascular disease, which has been a primary or underlying cause of death in 52.6% of RA patients [4]. Moreover, muscle weakness which is common in patients with RA, is likely to be exacerbated by HTN [2]. Despite these associations, blood pressure (BP) is not effectively controlled in RA patients, for example, 50% of RA with HTN patients maintained SBP above 140 mmHg even when taking antihypertensive drugs [5].…”
Section: Introductionmentioning
confidence: 99%